2012
DOI: 10.2139/ssrn.1689067
|View full text |Cite
|
Sign up to set email alerts
|

Noise as Information for Illiquidity

Abstract: We propose a market-wide liquidity measure by exploiting the connection between the amount of arbitrage capital in the market and observed "noise" in U.S. Treasury bonds-the shortage of arbitrage capital allows yields to deviate more freely from the curve, resulting in more noise in prices. Our noise measure captures episodes of liquidity crises of different origins across the financial market, providing information beyond existing liquidity proxies.Moreover, as a priced risk factor, it helps to explain cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 10 publications
0
63
0
Order By: Relevance
“…Past studies have suggested several important sources of arbitrage frictions: funding cost and constraints (Brunnermeier & Pedersen, 2009;Fontaine & Garcia, 2012), volatility (Pontiff, 2006) (Hu, Pan, & Wang, 2013;Kapadia & Pu, 2012), and counterparty risk (Gorton and Metrick, 2012;Mitchell & Pulvino, 2012). We select variables related to these arbitrage impediments to perform empirical tests.…”
Section: Market-wide Impediment Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have suggested several important sources of arbitrage frictions: funding cost and constraints (Brunnermeier & Pedersen, 2009;Fontaine & Garcia, 2012), volatility (Pontiff, 2006) (Hu, Pan, & Wang, 2013;Kapadia & Pu, 2012), and counterparty risk (Gorton and Metrick, 2012;Mitchell & Pulvino, 2012). We select variables related to these arbitrage impediments to perform empirical tests.…”
Section: Market-wide Impediment Variablesmentioning
confidence: 99%
“…Table 3 reports mean values of market-wide impediment variables for the normal and crisis periods, where the normal period includes both pre-and postcrisis periods. Results show that funding cost and constraints, TA B L E 3 Impediments to arbitrage and market integration Hu et al (2013); VIX is the volatility index; PSB is Pastor-Stambaugh bond liquidity index; PDCDS is the average rate of the CDS against primary dealers; LOIS is the yield spread between Libor and OIS rates; DPDPL is the change in net long-term security holdings by primary dealers; and CF is the net convertible fund flow. CSF measures the cash shortfall of primary dealers using the method in Daniel et al (2017).…”
Section: Cointegration Testsmentioning
confidence: 99%
“…This effect, however, is in part captured by our liquidity component. Indeed, the average fitting errors proxy for the slow moving capital, which is intimately linked with liquidity conditions in the bond market (Hu, Pan, and Wang 2013). liquidity conditions affect the level and dynamics of real rates. As a result, we include an (il)liquidity factor, so that real rates are driven by three factors: the X t =[r t , β t ] factors and the illiquidity factor l t .…”
Section: Bayesian Inferencementioning
confidence: 99%
“…In the case of fixed-income funds, we proxy for aggregate liquidity with the noise measure introduced by Hu, Pan, and Wang (2013). We use the negative of the measure so that higher values imply better liquidity conditions.…”
Section: Datamentioning
confidence: 99%
“…Then the yield curve is used to price all available bonds on a given day. The noise measure is the root mean squared deviation of the model-implied and observed yields (for details, see Hu, Pan, and Wang, 2013).…”
Section: Datamentioning
confidence: 99%